Sense–antisense miRNA pairs constitute an elaborate reciprocal regulatory circuit - Song, Yulong; Li, Lishi; Yang, Wenbing; Fu, Qiang; Chen, Wanying; Fang, Zeng; Li, Wen; Gu, Nannan; Zhang, Rui (Genome Research, 2020)
Antisense transcription of protein-coding genes has been increasingly recognized as an important regulatory mechanism of gene expression. However, less is known about the extent and importance of antisense transcription of noncoding genes. Here, we investigate the breadth and dynamics of antisense transcription of miRNAs, a class of important noncoding RNAs. Because the antisense transcript of a miRNA is likely to form a hairpin suitable as the substrate of ADARs, which convert adenosine to inosine in double-stranded RNAs, we used A-to-I RNA editing as ultrasensitive readout for antisense transcription of the miRNAs. Through examining the unstranded targeted RNA-seq libraries covering all miRNA loci in 25 types of human tissues, we identified 7275 editing events located in 81% of the antisense strand of the miRNA loci, thus uncovering the previously unknown prevalent antisense transcription of the miRNAs. We found that antisense transcripts are tightly regulated, and a substantial fraction of miRNAs and their antisense transcripts are coexpressed. Sense miRNAs have been shown to down-regulate the coexpressed antisense transcripts, whereas the act of antisense transcription, rather than the transcripts themselves, regulates the expression of sense miRNAs. RNA editing tends to decrease the miRNA accessibility of the antisense transcripts, therefore protecting them from being degraded by the sense-mature miRNAs. Altogether, our study reveals the landscape of antisense transcription and editing of miRNAs, as well as a previously unknown reciprocal regulatory circuit of sense–antisense miRNA pairs.